EFFECT OF DIMETHOATE ON SOME HISTOARCHITECTURE OF ARCHITECTURE OF FRESHWATER FISH TER FISH TER FISH OREOCROMIS MOSSAMBICUS OREOCROMIS MOSSAMBICUS OREOCROMIS MOSSAMBICUS (PETERS (PETERS, 1852) , 1852) - PRAGNA H. PARIKH; AYAZ RANGREZ; RUSHITA ADHIKARI-BAGCHI; BHAVIKA N. DESAI (The Bioscan, 2010)
The presence of Insecticide in the environment, due to extensive use in agriculture and their low degradation capacity, are of potential toxicological concern for fish. Histological studies have been widely used as biomarkers in the evaluation of the health of fish exposed to the pesticides, both in the laboratory as well as in the field studies. In the present study Adult fish of nearly similar weight (25 ± 1.9g) and length (15.5 ± 1.2cm) were exposed to two sub lethal concentrations i.e. 45.0 µg/L and 22.5µg/L of dimethoate for 21 days. The treated fish groups were compared with the control group for the histological changes in the selected tissues (Gills, Liver, Kidney, and muscle) and marked changes were observed.